2022
DOI: 10.2903/j.efsa.2022.7259
|View full text |Cite
|
Sign up to set email alerts
|

Scientific advice related to nutrient profiling for the development of harmonised mandatory front‐of‐pack nutrition labelling and the setting of nutrient profiles for restricting nutrition and health claims on foods

Abstract: Following a request from the European Commission, the EFSA Panel on Nutrition, Novel Foods and Food Allergens (NDA) was asked to deliver scientific advice related to nutrient profiling for the development of harmonised mandatory front-of-pack nutrition labelling and the setting of nutrient profiles for restricting nutrition and health claims on foods. This Opinion is based on systematic reviews and meta-analyses of human studies on nutritionally adequate diets, data from the Global Burden of Disease framework,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 165 publications
(266 reference statements)
0
33
0
1
Order By: Relevance
“…The maximum amount of these types of meat is usually given as up to 500 g/week (e.g., Finland, Sweden), or less than twice weekly (e.g., Malta) [ 14 ]. The recommendations of many countries mention fish, eggs, legumes, mycoprotein-based foods, and seitan as meat substitutes [ 2 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The maximum amount of these types of meat is usually given as up to 500 g/week (e.g., Finland, Sweden), or less than twice weekly (e.g., Malta) [ 14 ]. The recommendations of many countries mention fish, eggs, legumes, mycoprotein-based foods, and seitan as meat substitutes [ 2 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is also recommended to consume very little, if any, processed meat [ 13 ]. The European Food Safety Authority (EFSA) analysed the most recent systematic reviews of prospective cohort studies and estimated that the risk of chronic diseases, especially cancer, increases at a consumption of 100–120 g/day of unprocessed red meat and 50 g/day of processed meat [ 2 ]. These amounts are above most current recommendations in European national FBDGs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ahead of this, the European Commission has asked the European Food Safety Authority (EFSA) to provide scientific advice on nutrient profiling, based on which a harmonized FoPNL could be developed. The report concluded that saturated fat, added and free sugar and sodium should be included due to their adverse health effects when consumed in excess, whereas dietary fiber and potassium are currently consumed in too small amounts (Turck et al, 2022). However, the advice does not entail the creation of a new model to rank nutrients, nor does it offer recommendations on the existing models that have already been implemented.…”
Section: Introductionmentioning
confidence: 99%
“…Folate is an umbrella term describing a series of compounds that have similar structures and biological activities as folic acid. Folate is essential for the metabolism of amino acids, as well as for DNA and RNA synthesis. , However, dietary folate intake in European populations is often insufficient . Deficiency of folate is associated with a series of developmental, immune, and neurological disorders, such as neural tube defects and anemia .…”
Section: Introductionmentioning
confidence: 99%